Implementing IFRS and Financial Statements Audit: Prospects for Business Management - Afanasieva, I. I.; Ovsiuk, N. V.; Voroshylov, D. S. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article highlights the prospects for the implementation of international financial reporting standards (IFRS) in Ukraine, as well as the features of auditing financial reporting indicators compiled in accordance with IFRS requirements, which will be crucial for making decisions to improve business management efficiency. The positive impact of IFRS on the quality of financial reporting of enterprises has been confirmed in studies by many national and foreign scientists. However, IFRS are subject to regular updates, primarily in terms of recognition and presentation of accounting objects, so enterprises using IFRS must make changes in accounting policies, as well as disclose information about the potential impact of these changes on the accuracy of coverage of economic facts in the reporting. Auditing of IFRS-based reporting involves analysis of potential risks inherent in the first application of IFRS, as well as the compliance of the UA iXBRL Taxonomy reporting indicators with IFRS. The authors demonstrated the growing number of EU companies using IFRS, as this guarantees better transparency, accuracy and comparability of financial reporting indicators. The professional judgment of accounting specialists and auditors has a significant impact on the reliability and accuracy of financial reporting of business entities. The lack of strict regulation in IFRS and the possibility of using professional judgment will help make IFRS-based reporting more transparent and understandable for users. The transition of business entities to IFRS involves additional efforts and costs, as enterprises have to make certain changes in accounting formats and practices. However, the experience of foreign countries that have introduced international standards proves that such a transition provides tangible benefits to various business sectors. During the audit of financial statements, it is important to identify potential risks, in particular those associated with failure to detect errors when an enterprise first applies IFRS to prepare financial statements, which will affect the reliability of the information obtained and the correctness of reporting in the future.